Treatment of halitosis antibiotics or probiotics: Halitosis of dental origin - antibiotics or probiotics - Robo, Ilma; Heta , Saimir; Hysi , Joana; Balla , Iriana; Alliu , Nevila (International Journal of Dental Research, 2024)
Background: Halitosis as the primary causative source is thought to be the oral cavity, including here not only pathologies of dental origin such as caries or periodontitis, but also including the effect of a diet rich or not in nitrite products, which is reflected in the produced saliva, with the effect of in the oral cavity. Halitosis originates from pathologies of different systems, mainly mentioning the gatointestinal one. If these pathologies have a new treatment trend such as the application of probiotics, the question is whether or not they can be used for halitosis treatment. Collecting data from published literature sources about the possibility of treating halitosis with probiotics is another goal of this study.Main body of the abstract: The study is of the review type with the aim of knowing the data published in the literature on the possibility of treating halitosis through the application of probiotics. Probiotics are seen as the newest possibility for the treatment of periodontal pathologies and not only but also carious processes. Based on the literature data, the initial source of halitosis is exactly periodontal pathologies and carious processes, to continue further with problems related to pathologies of different systems of the body. The time of selection for the articles included in this study was 5 years of publications, so the purpose is the analysis of the data published in the literature on the Pubmed page on this topic, in the last 5 years, considering the trend of scientific research on this topic. Based on these key word combinations and based on the application of search filters, 15 articles were selected for further analysis on this topic.Short conclusion: Studies about probiotics should be channeled into the "in vivo" type for real clinical results. Probiotics should come up with specific names of effective bacteria versus specific names of pathogenic bacteria of oral pathologies. The family of lactobacilli is effective against specifically p. gingivalis, but against S. mutans this data is missing. In about 7% of cases, halitosis is caused by gastrointestinal disorders, and as an oral cause of halitosis, there is no specific division from only caries or only periodontitis.